2019
DOI: 10.3897/bdj.7.e38292
|View full text |Cite
|
Sign up to set email alerts
|

The role of ant nests in European ground squirrel’s (Spermophilus citellus) post-reintroduction adaptation in two Bulgarian mountains

Abstract: The European ground squirrel (Spermophilus citellus) is a vulnerable species, whose populations are declining throughout its entire range in Central and South-Eastern Europe. To a great extent, its conservation depends on habitat restoration, maintenance and protection. In order to improve the conservation status of the species, reintroductions are increasingly applied. Therefore, researchers focus their attention on factors that facilitate these activities and contribute to their success. In addition to the w… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
4
0

Year Published

2022
2022
2023
2023

Publication Types

Select...
3

Relationship

1
2

Authors

Journals

citations
Cited by 3 publications
(4 citation statements)
references
References 24 publications
0
4
0
Order By: Relevance
“…Importantly, in the current guidelines of souslik conservation, the issue of the competition with other species and its impact on spatial distribution is not considered. In turn, there is evidence in the literature that interspecies interactions may be important for the souslik population 21 . In periods of low abundance, when the survival of the population is at risk, the sousliks may have different habitat preferences than in periods of the abundant population 20 .…”
Section: Discussionmentioning
confidence: 99%
See 1 more Smart Citation
“…Importantly, in the current guidelines of souslik conservation, the issue of the competition with other species and its impact on spatial distribution is not considered. In turn, there is evidence in the literature that interspecies interactions may be important for the souslik population 21 . In periods of low abundance, when the survival of the population is at risk, the sousliks may have different habitat preferences than in periods of the abundant population 20 .…”
Section: Discussionmentioning
confidence: 99%
“…It has also been reported that unexpected interspecies interactions may sometimes be important for the habitat preferences of the souslik during the colonization of a new area, e.g. in Bulgaria, Lasius flavus anthills were chosen by the souslik as preferred places to locate burrows 21 . It can therefore be expected that the presence of another mammalian burrowing species, such as the mole, may also affect the souslik, especially in critical periods of low population abundance.…”
Section: Introductionmentioning
confidence: 99%
“…Recapture sessions were organised monthly. The stress levels, spatial behaviour and parasite loads were monitored and most of the results are published ( Kachamakova et al 2019 , Kachamakova and Koshev 2021 ) or in preparation. Аt every first animal capture during both translocation efforts and recapture sessions, standard morphometric measurements were taken with a vernier caliper with 1 mm accuracy, except for some cases where the measurement was not possible due to technical issues.…”
Section: Methodsmentioning
confidence: 99%
“…For example, they impact resource heterogeneity within a landscape by creating diversity in nutrient concentrations (Dostál, 2007) and thus potentially enhancing the restoration of degraded grasslands (Lane & BassiriRad, 2005). Their nests may foster recolonization by other organisms, mainly plants but also fauna (Kachamakova et al, 2019; Nicolai, 2019), throughout the degraded ecosystem. Moreover, their impacts are detected not only during nest occupation but also up to more than 20 years after colony disappearance (Kristiansen & Amelung, 2001; Lane & BassiriRad, 2005), thus increasing their spatial and temporal environmental impact.…”
Section: Ants In Restoration Ecologymentioning
confidence: 99%